Théorie du droit et front écologique : apport à la (re)définition de la justice environnementale - Nadia Belaidi (Développement Durable et Territoires)
What are the processes and dynamics of an environmental justice? This is the resulting question of the law and geography connexions when we wanted to consider strategy of conquest operated on a protected area (Table Mountain National Park, Cap Town, South Africa). This link showed, on one hand, that geographical terminology depends on law as social process and, on the other hand, that defintion of the notion of environmental justice requires a global conception that can offer a Law and Geography combined analysis.